Analisis Komparatif Model CIPP dan Model Four Level dalam Evaluasi Program Pendidikan - Muhammad Saleh; Nur Khalisah Latuconsina (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to conduct a comparative analysis of the CIPP Model (Context, Input, Process, Product) and the Four Levels Model (Reaction, Learning, Behavior, Results) in educational program evaluation. This research employs a qualitative approach using a library research method, drawing on relevant books, scientific journal articles, and previous studies. Data analysis was conducted using content analysis through the processes of data collection, categorization, and comparative analysis of both evaluation models. The findings indicate that the CIPP Model has a comprehensive evaluation characteristic and is oriented toward decision-making, as it covers all stages of a program, including context, input, process, and product. In contrast, the Four Levels Model focuses more on measuring program effectiveness based on changes in participants, namely reaction, learning, behavior, and final results. Both models have their own strengths and limitations; therefore, they are not mutually exclusive but rather complementary depending on the evaluation objectives. In conclusion, the CIPP Model is more suitable for evaluating educational programs that are systematic and comprehensive, while the Four Levels Model is more appropriate for training and competency development evaluations. The integration of both models can provide a more comprehensive evaluation outcome in improving the quality of education.